PENGARUH LIKUIDITAS, PERTUMBUHAN PERUSAHAAN, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN - Rima Choirunisari, (2020)
This research is using quantitative study aimed to examine the effect of liquidity, company's growth, and previous year's audit opinion on going concern audit opinion. The sample in this study amounted to 81 manufacture sector companies found on the Indonesia Stock Exchange and the website of each company for the period 2016-2018 which were selected using the purposive sampling method. Hypothesis testing in this study was used Logistic Regression Analysis using SPSS analysis tool with a significant level of 5%. The result of hypothesis testing showed that, liquidity had negative significant effect on going concern audit opinion, company's growth had no significant effect on going concern audit opinion, previous year's audit opinion had positive significant effect on going concern audit opinion.